A passive leg-support exoskeleton adversely affects reactive balance after simulated slips and trips on a treadmill. (April 2023) - Dooley, Stephen; Kim, Sunwook; Nussbaum, Maury A.; Madigan, Michael L.
Abstract: Occupational exoskeletons have become more prevalent as an ergonomic control to reduce the physical demands of workers. While beneficial effects have been reported, there is relatively little evidence regarding potential adverse effects of exoskeletons on fall risk. The purpose of this study was to investigate the effects of a leg-support exoskeleton on reactive balance after simulated slips and trips. Six participants (three females) used a passive, leg-support exoskeleton that provided chair-like support in three experimental conditions (no exoskeleton, low-seat setting, high-seat setting). In each of these conditions, participants were exposed to 28 treadmill perturbations from an upright standing posture simulating a backward slip (0.4–1.6 m/s) or a forward trip (0.75–2.25 m/s). The exoskeleton increased the probability of a failed recovery, and adversely affected reactive balance kinematics, after simulated slips and trips. After simulated slips, the exoskeleton decreased initial step length 0.039 m, decreased mean step speed 0.12 m/s, anteriorly displaced touchdown position of the initial recovery step by 0.045 m, and decreased PSIS height at initial step touchdown by 1.7 % sof its standing height. After simulated trips, the exoskeleton increased trunk angle at step 2.4 degrees, and decreased initial step length 0.033 m. These effects appeared to result from the exoskeleton inhibiting regular stepping motion due to its posterior placement on the lower limbs, added mass, and mechanical constraints on participant movement. Our results suggest care may be needed among leg-support exoskeleton users when at risk of slips or trips and motivate potential exoskeleton design modifications to reduce fall risk.